Analisis Faktor Yang Berhubungan Dengan Kecemasan Dalam Menghadapi Persalinan di Puskesmas Aek Parombunan Kecamatan Sibolga Selatan Kota Sibolga - Barus, Maghdalena; Hutagalung, Juliana (Miracle Journal, 2024)
A woman's anxiety levels during pregnancy may be affected by her age, degree of education, employment, marital status, fear of giving birth, and her history of miscarriages. Factors such as a woman's age, level of education, employment, parity, obstetric status, gestational age, health behavior, ANC history, and her husband's support are all linked to her anxiety throughout pregnancy, according to several studies. This study falls under the category of analytical observational research since it does not treat research subjects in any way to help researchers understand the issue more thoroughly. This study used a cross-sectional design and was a survey in nature. The 144 moms who participated in the ANC procedure in April 2024 at the Aek Parombunan Community Health Center in the South Sibolga District of Sibolga City made up the study's population. Sixty participants were used as samples in this study, which used the Slovin formula for sample selection. We employed a sequential sampling technique. The research and discussion led to the following conclusions: status is related to anxiety during childbirth (p = 0.027), ANC history is related (p = 0.015), history of pregnancy complications is not related (p = 0.775), and at Aek Parombunan Community Health Center, there is a statistical relationship between husband's support and anxiety (p = 0.008). It is anticipated that the UPT of the Aek Parombunan Community Health Center will be able to offer counseling to pregnant women regarding the prevalence, effects, and prevention of anxiety in this population.